Roles of CpcF and CpcG1 in Peroxiredoxin-Mediated Oxidative Stress Responses and Cellular Fitness in the Cyanobacterium Synechocystis sp. PCC 6803 - Oh, Sookyung; Montgomery, Beronda L. (Frontiers in Microbiology, 2019)
As a component of the photosynthetic apparatus in cyanobacteria, the phycobilisome (PBS) plays an important role in harvesting and transferring light energy to the core photosynthetic reaction centers. The size, composition (phycobiliprotein and chromophore), and assembly of PBSs can be dynamic to cope with tuning photosynthesis and associated cellular fitness in variable light environments. Here, we explore the role of PBS-related stress responses by analyzing deletion mutants of cpcF or cpcG1 genes in Synechocystis sp. PCC 6803. The cpcF gene encodes a lyase that links the phycocyanobilin (PCB) chromophore to the alpha subunit of phycocyanin (PC), a central phycobiliprotein (PBP) in PBSs. Deletion of cpcF (i.e., ΔcpcF strain) resulted in slow growth, reduced greening, elevated reactive oxygen species (ROS) levels, together with an elevated accumulation of a stress-related Peroxiredoxin protein (Sll1621). Additionally, ΔcpcF exhibited reduced sensitivity to a photosynthesis-related stress inducer, methyl viologen (MV), which disrupts electron transfer. The cpcG1 gene encodes a linker protein that serves to connect PC to the core PBP allophycocyanin. A deletion mutant of cpcG1 (i.e. ΔcpcG1) exhibited delayed growth, a defect in pigmentation, reduced accumulation of ROS, and insensitivity to MV treatment. By comparison, ΔcpcF and ΔcpcG1 exhibited similarity in growth, pigmentation, and stress responses; yet, these strains showed distinct phenotypes for ROS accumulation, sensitivity to MV and Sll1621 accumulation. Our data emphasize an importance of the regulation of PBS structure in ROS-mediated stress responses that impact successful growth and development in cyanobacteria.